Improving Maternal Role on Toddler Oral Hygiene in Integrated Service Center (Posyandu) Beber, Cirebon, Indonesia through Participatory Approach Assistance - Yenny Lisbeth Siahaan; Sekar Restuning; Ni Made Yuliana; Jendri Mamangkey (International Journal of Health and Pharmaceutical (IJHP), 2021)
Poor dental health on children including caries causes pain and difficulty in chewing. This study aimed to analyze the effect of assistance model on mothers to impove toddler oral health aged 2-5 years old. This research employed quasi-experiment through pretest and posttest approach intervention. The samples were mothers having 2-5 years old toddlers who met inclusion criteria including having PHP-M teeth index score of 40, willing to be involved, the mothers have at least junior high school education level and living in the Posyandu are. Meanwhile, the exclusion criteria was mothers who rarely visited Posyandu. Furthermore, data were analyzed using univariate and bivariate. If the data were not normally distributed, then Wilcoxon test would be done. Difference obtained between before and after the assistance model was provided to the mothers with significance value of p=0.001 (p<0.05). This indicates that assistance model caused changes on mothers’ knowledge at Posyandu. Same results were obtained from attitude, skills and PHP-M index score before and after the intervention with significance value of P=0.001 (p<0.05). This shows that assistance model caused changes on attitude, skills and decrease of toddlers’ PHP-M index score at Posyandu Beber. The outcome of the current research obtained that assistance model is proven to be more effective in improving toddler oral hygiene than extension that was carried out at Posyandu.